Nepal-India Power Exchange: A Critical Review - Mishra, Subhash K. (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Nepal-India power exchange has long been taking place. The effectiveness of the exchange scenario, however, is not very encouraging. The main reason for this is the lack of physical infrastructures and sound power transaction modalities. In this article, Nepal-India power exchange is critically reviewed with regards to the physical infrastructures and in the Nepalese perspectives. Key words: Power exchange; Power pool; Transmission lines; Grids; AC; HVDC; Load shedding; Synchronization DOI: 10.3126/hn.v5i0.2479 Hydro Nepal Vol. 5, July 2009 Page:18-20